(untitled) (Research, Society and Development, 2023)
The objective was to understand the importance of Community Health Agents (CHA) in actions to monitor vaccination in children under 5 years of age, seeking to list, through the scientific literature, the challenges and barriers that hinder the scope of vaccination campaigns and the intervention strategies of these professionals. It is an integrative literature review of a descriptive-exploratory nature, in which searches were carried out through the CINAHL, Embase, SCOPUS and MEDLINE databases. Initially, 163 studies were found and, according to the defined criteria, this number was reduced to 82. Furthermore, 27 were selected by reading the titles and abstracts, of which, with the full analysis, 9 were chosen to compose the final sample. The importance of these professionals in the development of multifaceted strategies to contact children and increase vaccination rates was highlighted, thus ensuring greater access to health services and policies, as well as awareness and mobilization of the community. This field of investigation was chosen due to the fact that there are gaps in knowledge about access to immunization programs, thus requiring community agents trained to detect children with delayed vaccination and to pass on guidance on the importance and benefits of this action.